PENYEMBUHAN DAN PERBAIKAN MORAL WANITA PENGHIBUR - Jodi Adam; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2023)
Globalization has brought many significant changes and impacts to the world, both positive and negative. On the one hand, globalization has brought technological advances and information that enable access to faster and easier information and communication, as well as increasing international trade and foreign investments that can drive economic growth. On the other hand, globalization is also potentially exacerbating the social and economic disparity between strong and weak countries, as well as strengthening the influence of multinational forces and global organizations to make decisions that can affect human life. And free association is one of the effects of globalization itself. Promiscuity is a social phenomenon with such a variety of forms as murder, alcoholic beverages, smoking, brawling, and sexual promiscuity. Casual sex is one form of free association and the effects of casual sex: premature marriage, abortion, and HIV. HIV is a very lethal impact. The spread of HIV is free of the three factors: female entertainers, drug use, and poor dipper. Female entertainers are a form of sexual promiscuity. On the other hand, a lack of empathy for society leads to mental, psychological and biological problems for prostitutes. In this regard, empathy for female entertainers also plays a key role in promoting more inclusive and friendly social changes for individuals involved in tuna. In building empathy for female comforters, society needs to treat them with respect, tolerance, and understanding. Thus, it is hoped that a more inclusive and friendly social environment will be created for all individuals in society, through architecture. The project employs methods of juhani pallasmaa's theory